Identification and characterization of Pythium spp. at - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2010)
Pythium spp, cause severe bean root rots under cool and humid conditions. Poor soils and intensive cultivation compound the epidemics. There are more than 120 species reported globally some of which are very pathogenic meanwhile others are saprophytic. Yield losses due to Pythium outbreaks can be as high as 100% on susceptible varieties in the absence of control measures. Bean root rot caused by Pythium is the most devastating in Eastern & Central Africa where the intensity of bean production is high.